Globalisasi dan Isu-isu PAI di Indonesia: Respon dan Tantangan 2010-2020 - Sunandar, Dikdik; Ruswandi, Uus; Erihadiana, Mohamad (STAI AL-FALAH CICALENGKA, 2020)
This article aimed to explore the existence of islamic education on the middle of globalization era. This research which applied a descriptive qualitative method.Islamic education must still exist in yeast to give color and trend of globalization. Therefore, Islamic education must be developed both theories, ideas and concrete action in the arena of globalization. Global world may not be denied, even just to be faced with evidence of real performance. One of which is being used as Indonesian republican government policy is the implementation of the curriculum in 2013. The curriculum is known as thematic integrative curriculum. However, among the thinkers and practitioners in education curriculum concept store is still a big question whether the issue will be resolved through the Indonesian national curriculum in 2013? Answering this question needs a comprehensive review of the entire sub-system of education in Indonesia. Islamic education is an important part of a real existence in Indonesia from age to age. The findings showed that Islamic education a real need to provide effect and active coloring toward the advancement of science and technology, as urged in the globalization era. Keyword: Globalization, Islamic education, social issues Abstrak Artikel ini bertujuan untuk mengeksplorasi eksistensi pendidikan Islam ditengah-tengah era globalisasi. Penelitian ini menggunakan metode deskriptif kualitatifPendidikan Islam harus tetap eksis dalam memberikan warna dan ragi bagi trend globalisasi. Oleh sebab itu, pendidikan Islam perlu terus dikembangkan baik teori, pemikiran dan aksi nyata dalam percaturan globalisasi. Dunia global tidak mungkin dipungkiri, bahkan justru harus dihadapi dengan bukti kinerja nyata. Salah satu kebijakan pemerintah Republik Indonesia yaitu kurikulum pendidikan tahun 2013. Kurikulum ini dikenal dengan kurikulum tematik integratif. Namun demikian, konsep kurikulum ini masih menyimpan pertanyaan besar apakah masalah bangsa Indonesia akan teratasi melalui kurikulum 2013? Menjawab pertanyaan ini perlu kajian komprehensif dari seluruh subsistem pendidikan di Indonesia. Pendidikan Islam merupakan bagian penting yang eksistensinya di Indonesia nyata dari zaman ke zaman.penelitian ini menunjukan bahwa pendidikan Islam yang nyata ini perlu memberikan pengaruh nyata dan aktif mewarnai arah kemajuan sains teknologi sebagaimana didesak dalam era globalisasi. Kata kunci: globalisasi, isu-isu sosial, pendidikan Islam